Distinguishing between keto–enol and acid–base forms of firefly oxyluciferin through calculation of excited‐state equilibrium constants. Issue 30 (16th September 2014) - Falklöf, Olle; Durbeej, Bo
<x xml:space="preserve">Abstract</x> Although recent years have seen much progress in the elucidation of the mechanisms underlying the bioluminescence of fireflies, there is to date no consensus on the precise contributions to the light emission from the different possible forms of the chemiexcited oxyluciferin (OxyLH2) cofactor. Here, this problem is investigated by the calculation of excited‐state equilibrium constants in aqueous solution for keto–enol and acid–base reactions connecting six neutral, monoanionic and dianionic forms of OxyLH2. Particularly, rather than relying on the standard Förster equation and the associated assumption that entropic effects are negligible, these equilibrium constants are for the first time calculated in terms of excited‐state free energies of a Born–Haber cycle. Performing quantum chemical calculations with density functional theory methods and using a hybrid cluster‐continuum approach to describe solvent effects, a suitable protocol for the modeling is first defined from benchmark calculations on phenol. Applying this protocol to the various OxyLH2 species and verifying that available experimental data (absorption shifts and ground‐state equilibrium constants) are accurately reproduced, it is then found that the phenolate‐keto‐OxyLH– monoanion is intrinsically the preferred form of OxyLH2 in the excited state, which suggests a potential key role for this species in the bioluminescence of fireflies. © 2014 Wiley Periodicals, Inc.